(3OSJhQ GdeHJOFjfs - (3eMeO Hf QSJe GdcjdGfjs
(3ChdgG (B:s
(3hHYO agPG OSJhQ GdeHJOFjf ai UfGYI ef TOge (B((3?(B) (3Edi ESJfHGWg ef GdcJH , cJHg HGdYLdI ai CKfGA GdeYGdLI , YLdI GdhbJ dHYV GdENhGf s
(3BNQgG (B:s
(3WdGA ddSYaI , jMQb ROhGfO Whjd HbTQ QeGf JYLf HGdNd ChdkC hOgf GdhQO KGfjkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdJGH GdKGfi (B- (3U (B91 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdWHs